2017
DOI: 10.1177/1538574417744085
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Thromboangiitis Obliterans (Buerger’s Disease)

Abstract: Percutaneous transluminal angioplasty can be considered as a technically feasible and potentially effective treatment for patients with TAO and CLI, as well as a last resort for limb salvage when other options have failed. However, reintervention may be required, especially in patients who continue smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
0
16
0
2
Order By: Relevance
“…A study showed that if one continues to smoke, this can significantly affect the durability of the proposed intervention and the efficacy is dependent on the duration of abstinence from smoking. 42 The lower incidence of infragenicular restenosis in this study could be explained by the aggressive ballooning for higher than average pressures and longer duration. Hypothetically, this might result in periarterial sympathectomy and thus minimization of vasoconstriction, recoil and stenosis, all translating into improved long-term patency and durable ulcer healing.…”
Section: Discussionmentioning
confidence: 59%
“…A study showed that if one continues to smoke, this can significantly affect the durability of the proposed intervention and the efficacy is dependent on the duration of abstinence from smoking. 42 The lower incidence of infragenicular restenosis in this study could be explained by the aggressive ballooning for higher than average pressures and longer duration. Hypothetically, this might result in periarterial sympathectomy and thus minimization of vasoconstriction, recoil and stenosis, all translating into improved long-term patency and durable ulcer healing.…”
Section: Discussionmentioning
confidence: 59%
“…4 Even contemporary endovascular therapy might be able to serve as a potential option for TAO patients with lower limb symptoms. 4 Importantly, close monitoring is recommended, and endovascular re-intervention may be required to maintain clinical benefit, especially in patients who continue smoking. 4 Our case represents an example where a combination of inadequate vascular examination with poor knowledge of proximal vascular involvement in TAO and underestimation of the positive-even short-termed-effects of endovascular interventions in limb-threatening conditions led to delayed referral to vascular specialist and therapeutic intervention.…”
mentioning
confidence: 99%
“…4 Importantly, close monitoring is recommended, and endovascular re-intervention may be required to maintain clinical benefit, especially in patients who continue smoking. 4 Our case represents an example where a combination of inadequate vascular examination with poor knowledge of proximal vascular involvement in TAO and underestimation of the positive-even short-termed-effects of endovascular interventions in limb-threatening conditions led to delayed referral to vascular specialist and therapeutic intervention. To achieve better clinical results, integrated care in a multidisciplinary team with emphasis on smoking cessation, pain control, wound management, and social care by professionals, social workers, and family members is necessary.…”
mentioning
confidence: 99%
See 2 more Smart Citations